Evaluating the phenotypic responses of CRISPR/Cas9-edited Mentik Wangi rice mutants T1 focusing on GA20ox2 and OsCKX2 gene knockout - TILMIIDZAH SALMA FATHIN; ATMITRI SISHARMINI; ANIVERASRI APRIANA; TRI JOKO SANTOSO; AHMAD YUNUS (Society for Indonesian Biodiversity, 2024)
Abstract. Fathin TS, Sisharmini A, Apriana A, Santoso TJ, Yunus A. 2024. Evaluating the phenotypic responses of CRISPR/Cas9-edited Mentik Wangi rice mutants T1 focusing on GA20ox2 and OsCKX2 gene knockout. Biodiversitas 25: 2783-2790. Mentik Wangi is a local Indonesian rice variety with tall plant stature, making it susceptible to lodging and yield loss, necessitating trait improvements to overcome these weaknesses. Gene editing of GA20ox2 and OsCKX2 using CRISPR/Cas9 was conducted to improve the characteristics of Mentik Wangi. This study aimed to evaluate the phenotypic responses of T1 Mentik Wangi mutant lines generated through gene editing using the CRISPR/Cas9 system. Eighty-five mutant lines and wild-type plants were grown and observed in a greenhouse. Phenotypic traits were observed as quantitative traits, such as plant height, panicle length, total number of tillers, number of productive tillers, total number of grains, 1000-grain weight, heading date, and harvesting age; and qualitative traits, such as panicle type and panicle exsertion type. The results showed a decrease in plant height and panicle length in Mentik Wangi rice mutant lines. Several lines exhibited improvements in total tiller number, productive tiller number, total grain number, and 1000-grain weight. Mutant lines required longer to reach the generative phase and displayed differences in panicle type and panicle exsertion type. This study reported that the T1 mutant lines demonstrated distinct phenotypic responses indicating improvements in the desired traits.